Impacts of Magnetosheath High‐Speed Jets on the Magnetosphere and Ionosphere Measured by Optical Imaging and Satellite Observations. Issue 6 (21st June 2018) - Wang, Boyi; Nishimura, Yukitoshi; Hietala, Heli; Lyons, Larry; Angelopoulos, Vassilis; Plaschke, Ferdinand; Ebihara, Yusuke; Weatherwax, Allan
Abstract: Magnetosheath high‐speed jets (HSJs) are dayside upstream transient disturbances with enhanced flow velocity and dynamic pressure. They are associated with significant magnetopause perturbations, ultralow frequency waves in the dayside magnetosphere, and localized flow enhancements in the ionosphere. However, whether HSJs have corresponding dayside aurora signatures is still an open question. If auroral signatures are found, 2‐D structure and evolution of HSJ effects on the magnetosphere can be imaged in a much higher precision than possible by other means. In this study, eight HSJ events are identified by the THEMIS satellites located within ±1 MLT of the center of the field‐of‐view of the South Pole station all‐sky imager. In all of those cases, the HSJs are observed to have a nearly one‐to‐one relationship with individual localized discrete/diffuse auroral brightenings. The azimuthal size of HSJ‐related diffuse aurora signatures is ~800 km at 230‐km altitude in the ionosphere and ~3.7 Re in the magnetosphere, which is slightly larger but of the order of the cross‐sectional diameter of HSJs (~1 Re ). Furthermore, most of those aurora signatures have azimuthal motion, whose magnitude and direction agree with magnetosheath background flows. This study for the first time shows high‐resolution, two‐dimensional observations of localized structure and fast propagation of precipitation due to magnetosheath HSJs. We conclude that magnetosheath HSJs can have substantial impacts on the coupled magnetosphere‐ionosphere system, causing localized magnetospheric compression and aurora brightening, in a similar manner to responses during interplanetary shocks except with a smaller scale size. Key Points: We show, for the first time, auroral evolution due to magnetosheath HSJs in high‐resolution 2‐D imaging HSJs have substantial impacts on the coupled M‐I system, causing localized magnetospheric compression and aurora brightening Auroral imaging can determine the size and evolution of HSJ effects. The azimuthal speed is consistent with background sheath flow speed